Arthritis in the Canadian Aboriginal Population: North-South Differences in Prevalence and Correlates - C. Ng, MSc (1); S. Chatwood, MSc (2,3); T. K. Young, MD, PhD (3) (Centers for Disease Control and Prevention, 2011)
BackgroundInformation on arthritis and other musculoskeletal disorders among Aboriginal people is sparse. Survey data show that arthritis and rheumatism are among the most commonly reported chronic conditions and their prevalence is higher than among non-Aboriginal people.ObjectiveTo describe the burden of arthritis among Aboriginal people in northern Canada and demonstrate the public health significance and social impact of the disease.MethodsUsing cross-sectional data from more than 29 000 Aboriginal people aged 15 years and over who participated in the Aboriginal Peoples Survey 2006, we assessed regional differences in the prevalence of arthritis and its association with other risk factors, co-morbidity and health care use.ResultsThe prevalence of arthritis in the three northern territories ("North") is 12.7% compared to 20.1% in the provinces ("South") and is higher among females than males in both the North and South. The prevalence among Inuit is lower than among other Aboriginal groups. Individuals with arthritis are more likely to smoke, be obese, have concurrent chronic diseases, and are less likely to be employed. Aboriginal people with arthritis utilized the health care system more often than those without the disease.Conclusion: Aboriginal-specific findings on arthritis and other chronic diseases as well as recognition of regional differences between North and South will enhance program planning and help identify new priorities in health promotion.